Dampak Gerakan Literasi KM-4 di SDN Gaddong 2 - Satriawati Satriawati; R Supardi R Supardi; Nurhadifah Amaliyah; Kurniawati Buton; Kristin Lestari (Joong-Ki : Jurnal Pengabdian Masyarakat, 2023)
The purpose of writing this journal is to describe the impact of the literacy movement implemented at SD Negeri 2 Makassar. This aims to broaden students' insights and foster students' interest in reading, because reading various knowledge can lead to success. The teaching campus is a place where students are given the opportunity to gain experience in terms of teaching and can devote themselves to placement schools. Through this teaching campus, we are implementing the literacy movement at our placement school, SD Negeri Gaddong 2 Makassar. In the initial observation of the assignment, there were several students who were still passive in reading, paying attention to efforts to increase students' reading literacy with literacy movements, various kinds of activities related to literacy so that they could slowly foster students' love for the literacy movement. The activities implemented are the reading literacy movement 15 minutes before the learning process, and the implementation of a literacy club and the creation of a reading corner.